THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN EDUCATION - Mirzaakbarov Dilshod Davlatboyevich; Muhammedova Dilrabo Farhodjon qizi (Ustozlar uchun, 2025)
Artificial Intelligence (AI) has become one of the most transformative technologies of the 21st century. Its applications have extended into numerous fields, including healthcare, finance, transportation, and most significantly, education. As educational systems worldwide aim to improve learning outcomes and promote inclusive access to quality education, AI has emerged as a promising tool. This paper explores the role of artificial intelligence in modern education, emphasizing its benefits, applications, and associated challenges.